STUDI PERENCANAAN TANGGUL UNTUK PENGENDALI BANJIR SUNGAI PETAPAHAN KABUPATEN KUANTAN SINGINGI - Chitra Hermawan (JURNAL PLANOLOGI DAN SIPIL (JPS), 2019)
The Petapahan River is one of the rivers in Petapahan village which is prone to flooding that has an area of ​​89.23 km2 of watershed with a length of 16 km. Every flood incident due to overflow of the river has caused a significant risk flood such as almost 60 ha every year the fields are flooded, 143 houses are flooded, 56 km of national roads and roads are submerged in water. Planning flood control in the petapahan river can be done if the planned flood discharge in this river is known, so that the flood discharge can be designed to control the flood building in this study is the embankment. The embankment serves to hold flood discharge so that the overflow due to the petapahan river is expected to be the embankment, the embankment was designed using a flood discharge analysis plan using the HSS Gama I method using one rainfall post record, to calculate the hydraulic analysis using the Hec-Ras software in determining the river water profile, in calculating the embankment slope stability using the bishop method. The planned flood discharge analysis using the HSS Gama I method will produce a 25-year return flood discharge which is the basis for calculating the embankment dimensions, to calculate the overflowing water level on the river bank, then the 100 th re-flow of water is simulated into the hec-ras software. Based on the results of the calculation of the Hec-Ras application it is known that the water level that crosses a cliff is 150 cm. So for the construction of the flood retaining dike, the dimensions can be known as follows: Embankment height: 350 cm, Mercury width: 300 cm, Slope: 1: 2, Embankment Width: 500 cm From the calculation of Geo-Slope above for numerical Bishop Method Safety Factor > 1 which is 0.770 for granular soils which have a sliding angle of 33